Association between atrial fibrillation burden and cognitive function in patients with atrial fibrillation. (15th April 2023) - Tang, Sung-Chun; Liu, Yen-Bin; Lin, Lian-Yu; Huang, Hui-Chun; Ho, Li-Ting; Lai, Ling-Ping; Chen, Wen-Jone; Ho, Yi-Lwung; Yu, Chih-Chieh
Abstract: Background: Accumulating evidence has demonstrated an association between clinical atrial fibrillation (AF) and cognitive impairment. This study aimed to further clarify the impact of AF burden on cognitive function based on detailed electrophysiological recordings and standardized assessments of cognitive function. Methods: This prospective cohort study, conducted at the Cardiac Electrophysiology Clinic of a tertiary center, included patients with non-valvular AF. AF burden was evaluated using 14-day patch-based electrocardiography. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA). Results: Enrolled patients ( n = 253) were grouped according to the median AF burden (13.52%). Patients with higher AF burden were significantly older and had larger left atrium size, a worse ejection fraction, and a lower MoCA score than those with lower AF burden. Predictors of MoCA score included age, CHA2 DS2 -VASc score, AF burden, and Center for Epidemiologic Studies Depression Scale scores. The association between MoCA scores and AF burden remained significant after adjustment for demographic characteristics, underlying diseases, and echocardiographic parameters (standardized beta coefficient: −0.159, 95% confidence interval: −0.020 to −0.004, p = 0.004). Conclusion: AF burden is associated with cognitive function in patients with AF. Further studies are required to determine whether reducing AF burden can preserve cognitive function in these patients. Hightlights: This is the first prospective study to clearly demonstrate the association between cognitive function and AF burden in patients with AF. When treating a patient with AF, even if it cannot be eliminated, reducing AF burden may aid in preserving cognitive function. Defining AF burden as the percentage of time spent in AF may be easier and more appropriate for evaluating the severity of AF than defining based on the longest AF duration or number of AF events. The effects of AF burden on cognitive function appear to become more evident as the CHA2 DS2 -VASc score increases.